Pembentukan Karakter Pribadi Dan Sosial Di Pondok Pesantren Al-Hassan Rembang - Ainani, Wilda Qorri; Muizzuddin, M. (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
Character education serves as a fundamental pillar in shaping a generation that is not only intellectually capable but also morally grounded. Islamic boarding schools (pesantren), as traditional Islamic educational institutions, hold a strategic role in cultivating character, particularly for students from underprivileged family backgrounds. This study aims to describe and analyze the character values instilled and the processes of character formation at Pondok Pesantren Al-Hassan Tuyuhan, Pancur, Rembang. A qualitative case study approach was employed, utilizing participatory observation, in-depth interviews, and documentation for data collection. The findings reveal that key character values promoted include religiosity, discipline, responsibility, empathy, and independence. These values are nurtured through modeling, habituation, and intensive mentoring. The structured and religiously immersive environment of the pesantren enables a holistic character-building process. This study reinforces the significance of pesantren as a vital institution for character education amidst the growing moral challenges of the modern era.